Analisis hubungan kepercayaan, persepsi kemudahan penggunaan, persepsi manfaat, persepsi resiko dan keinginan membeli online anggota kaskus.us dalam pembelian online: Studi kasus: FJB kaskus.us - Ardikoesoema, Nurmansyah (EcoProfit: Sustainable and Environment Business, 2024)
This study applies qualitative methods as a theoretical basis for evaluating perceptions about ease of use and perceptions about benefits, which are strengthened by external variables, namely trust, in influencing the intention of Kaskus.us members to make purchase transactions on the Kaskus.us Buying and Selling Forum. The target population in this research is all Kaskus.us members who have shared any information on the Kaskus.us Buying and Selling Forum. The research methodology applied was purposive sampling and convenience sampling with structural equation modeling (SEM) analysis techniques. There were 200 respondents who overall stated that trust had a significant influence on online purchasing intentions. The research results also show that ease of use and benefits have a significant influence on online purchase intentions at the Kaskus.us Buying and Selling Forum. In general, the aim of this research is to analyze the influence of perceived ease of use, perceived usefulness, and trust on the intention to make online purchases among Kaskus.us members. By applying, 200 respondents who were active members of the Kaskus.us Buying and Selling Forum were included. The results show that trust, ease of use, and perceived usefulness significantly influence respondents' intention to make online purchases through the platform.